Strategy for Developing Business Kebun Latte Restaurant As A Culinary Tourism Destination - Rafi Dharmawan; Arif Imam Suroso; Sufrin Hannan (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Kebun Latte Restaurant has a concept of a teak plantation atmosphere and offers a diverse menu, making it one of the top choices for culinary tourism. However, Kebun Latte Restaurant has experienced a decline in revenue over the past three years, and there are several revenue streams that have not been maximized. Given the modern lifestyle trends of today's society, the restaurant company must anticipate changes and implement business model development strategies to enhance competitiveness and ensure the company remains a sustainable choice as a culinary tourism destination..Purpose: This research aims to identify the condition of the company using the business model canvas, then formulate alternative strategies so as to produce priority strategy recommendations that are implemented as a new business model formulation for Kebun Latte restaurant.Design/methodology/approach: This research was conducted from August 2023 to September 2024 and involved five respondents who had five years of experience in the tourism industry, particularly in the restaurant sector. In addition, the information received was processed using the business model canvas method, IFE and EFE, IE Matrix, SWOT analysis and Analytical Hierarchy Process (AHP).Finding/Result: The results of the study show nine elements of the business model canvas at Kebun Latte. The SWOT analysis shows 10 alternative strategies, and based on the AHP analysis, there are three strategic priorities, namely: improving marketing by highlighting the Instagrammable outdoor concept, maintaining and improving product quality, and developing products towards sustainability. These results provide changes in the formulation of the new version of the business model canvas.Conclusion: The results of this study provide strategic priorities to be implemented by the company, including increasing marketing by emphasizing the concept of instagrammable outdoors, maintaining and improving product quality and developing products towards sustainability. This affects the development of the 6 elements of the business model canvas.Originality/value (State of the art): The new Kebun Latte restaurant business model has a competitive advantage as a culinary tourism destination, namely the existence of sustainable products supported by an instagrammable outdoor concept. Keywords: analytical hierarchy process, business model canvas, culinary tourism, swot, strategy development